Archaeological evidence for hunter-gatherers mobility and diet changes during eighteen and nineteen centuries in the central Patagonian Atlantic coast - Gomez Otero, Julieta (2015)
The information discussed supports the less intensive use of these littoral sectors and their resources during equestrian times. The more probable explanations would be the mobility changes derived from the horse ecology and requirements (especially water), and the reduction in the acquisition costs of their prey. In the future we expect to explore these hypotheses through more and better archaeological evidence.